2007
DOI: 10.1016/j.ymgme.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous development of intestinal and colonic atrophy and inflammation in the carnitine-deficient jvs (OCTN2−/−) mice

Abstract: Carnitine is essential for transport of long-chain fatty acids into mitochondria for their subsequent β-oxidation, but its role in the gastrointestinal tract has not been well described. Recently several genetic epidemiologic studies have shown strong association between mutations in carnitine transporter genes OCTN1 and OCTN2 and a propensity to develop Crohn's disease. This study aims to investigate role of carnitine and β-oxidation in the GI tract. We have studied the gastrointestinal tract effects of carni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…It has been reported that SLC22A genes are high susceptibility genes in IBD, located at the so-called IBD locus 5 (IBD5) and that genetic polymorphisms within this region contribute to the inflammatory phenotype (Waller et al, 2006;Cucchiara et al, 2007;Silverberg et al, 2007). These observations are consistent with a mouse study showing that homozygous inactivation of Octn2 resulted in spontaneous development of colitis (Shekhawat et al, 2007). Decreased expression levels of Octn2 and another carnitine transporter Atb0ϩ were also shown to be associated with development of an inflammatory condition in rats (D'Argenio et al, 2006).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…It has been reported that SLC22A genes are high susceptibility genes in IBD, located at the so-called IBD locus 5 (IBD5) and that genetic polymorphisms within this region contribute to the inflammatory phenotype (Waller et al, 2006;Cucchiara et al, 2007;Silverberg et al, 2007). These observations are consistent with a mouse study showing that homozygous inactivation of Octn2 resulted in spontaneous development of colitis (Shekhawat et al, 2007). Decreased expression levels of Octn2 and another carnitine transporter Atb0ϩ were also shown to be associated with development of an inflammatory condition in rats (D'Argenio et al, 2006).…”
supporting
confidence: 77%
“…The OCTN2 protein is encoded by the IBD5 locus and polymorphisms in the SLC22A5 coding regions have been linked to IBD pathology (Russell et al, Waller et al, 2006;Cucchiara et al, 2007;Silverberg et al, 2007). In rats, a decrease in Octn2 expression levels triggers inflammation of the gastrointestinal tract (Shekhawat et al, 2007), possibly due to an aberration of carnitine transport and fatty acid metabolism (D'Argenio et al, 2006). It is interesting to note that a decrease in mRNA expression of OCTN2 was recently reported in the sigmoid region of UC colon (Noble et al, 2008), although to a lesser extent than to the decrease observed here in colon and terminal ileum (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by recent findings of spontaneous development of intestinal atrophy and inflammation in jvs mice, demonstrating an obligatory role of OCTN2 in the maintenance of normal intestinal morphology (11).…”
Section: Introductionsupporting
confidence: 65%
“…This substance showed a strong protective effect in gastric disorders of rats (152). As found in mice deficient in specific carnitine transporters, the lack of carnitine leads to spontaneous atrophy of epithelial cells in the small intestine and colon inflammation (153). In old rats, dietary administration of carnitine for 21 days contributed to significant reduce in formation of LPO products and improved activity of antioxidant enzymes -superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase.…”
Section: Intraepithelial Lymphocytes Of Chickens Are Represented By Amentioning
confidence: 85%